Torque-based gravity compensation using regression for tracing trajectory - Vamsi, Grandhi (Nanyang Technological University, 2022)
The surge in the number of robotic applications in the industry 4.0 era has led to myriads of applications, research experiments involving human-robot interaction. Hence it is essential to move towards actuators and robots that are compliant for the safety of the humans involved in the workspace. Gravity compensation in a robotic arm, aids to decrease the load on the actuator and increases the robustness of the actuator in tracing a reference trajectory. This report focuses on gravity compensation using torque-based control complemented with position control for a compliant actuator without any prior knowledge of the description of the payload. Multivariate linear regression was used to regress the commanded torque using torque control with an accuracy of 98.9%.